Seamless stainless steel tube and manufacturing method thereof

By optimizing the composition and heat treatment technology of stainless steel seamless steel pipes, an appropriate phase structure was formed, and the corrosion resistance of steel pipes for oil wells in the existing technology was solved in the existing technology under severe corrosion environments, and high-temperature carbon dioxide resistance, low-temperature SSC resistance and acid resistance are achieved. Excellent corrosion resistance in the environment, high strength and low temperature toughness.

CN119278288APending Publication Date: 2025-01-07JFE STEEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380042748.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-03-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing stainless steel seamless steel pipes for oil wells are insufficient in corrosion resistance under high temperature, carbon dioxide, chloride ions and hydrogen sulfide and other harsh corrosion environments, especially in low temperatures, the corrosion resistance of sulfide stress cracking and acid environments. accomplish.

Method used

By optimizing the composition of components, it contains Cr, Mo, Sn, Co, Ca, and limiting the phase fraction of Ni, combined with quenching-tempering treatment, it forms appropriate martensite, ferrite and residual austenite phase structures, improving the The yield strength and low-temperature toughness of steel pipes enhance their high-temperature carbon dioxide corrosion resistance, low-temperature SSC resistance and corrosion resistance in acid environments.

Benefits of technology

It has achieved excellent corrosion resistance of carbon dioxide at high temperature, SSC at low temperature and corrosion resistance in acid environments. It has yield strength of more than 758MPa and low temperature cabbage absorption energy of more than 40J. It is suitable for use in harsh environments such as oil wells. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151530850000211
    Figure BDA0005151530850000211
  • Figure BDA0005151530850000221
    Figure BDA0005151530850000221
  • Figure BDA0005151530850000231
    Figure BDA0005151530850000231
Patent Text Reader

Abstract

The stainless steel seamless steel pipe provided by the invention has high strength and excellent low-temperature toughness and corrosion resistance. The stainless steel seamless pipe has a prescribed component composition, has a martensite phase content of 30% or more, a ferrite phase content of 50% or less, and a retained austenite phase content of 40% or less in volume fraction, and has a yield strength of 758 MPa or more and a Charpy absorption energy vE-10 at-10 DEG C of 40 J or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a stainless steel seamless pipe suitable for use in oil wells and gas wells (hereinafter referred to as oil wells). The present invention particularly relates to a stainless steel seamless pipe having improved 2 ), chloride ion (Cl - ) in a high temperature and severe corrosive environment, in an environment containing hydrogen sulfide (H 2 S) environment with medium corrosion resistance stainless steel seamless steel pipe. Background Art

[0002] Stainless steel seamless pipes are widely used for oil well steel pipes, etc. Oil well steel pipes are required to have excellent yield strength and, in recent years, excellent low-temperature toughness as oil fields are developed in cold regions.

[0003] Furthermore, from the perspective of energy depletion expected in the near future, oil wells are being developed in deep oil fields, in environments containing carbon dioxide, and in so-called acidic hydrogen sulfide-containing environments, which have never been considered before. Therefore, high corrosion resistance is also required for steel pipes for oil wells.

[0004] In the past, in the 2 and Cl - In oil fields and gas fields under the environment of , 13Cr martensitic stainless steel pipes are generally used as oil well steel pipes used for mining. However, recently, the development of oil wells with higher temperatures (up to 200°C) is underway, and the corrosion resistance of 13Cr martensitic stainless steel pipes is sometimes insufficient. Therefore, there is an urgent need for an oil well steel pipe with higher corrosion resistance that can be used in such an environment.

[0005] In response to such urgent expectations, for example, Patent Document 1 proposes a stainless steel for oil wells having the following composition: in terms of mass %, it contains C: less than 0.05%, Si: less than 1.0%, Mn: 0.01-1.0%, P: less than 0.05%, S: less than 0.002%, Cr: 16-18%, Mo: 1.8-3%, Cu: 1.0-3.5%, Ni: 3.0-5.5%, Co: 0.01-1.0%, Al: 0.001-0.1%, O: less than 0.05% and N: less than 0.05%, wherein Cr, Ni, Mo and Cu satisfy a specific relationship.

[0006] In addition, Patent Document 2 proposes a high-strength stainless steel seamless steel pipe for oil wells, having the following composition: in terms of mass%, it contains C: 0.005-0.05%, Si: 0.05-0.50%, Mn: 0.20-1.80%, P: less than 0.030%, S: less than 0.005%, Cr: 12.0-17.0%, Ni: 4.0-7.0%, Mo: 0.5-3.0%, Al: 0.005-0.10%, V: 0.005-0.20%, Co: 0.01-1.0%, N: 0.005-0.15%, O: less than 0.010%, and Cr, Ni, Mo, Cu, C, Si, Mn, and N satisfy specific relationships.

[0007] In addition, Patent Document 3 proposes a high-strength stainless seamless steel pipe for oil wells, which has the following composition: in terms of mass%, it contains C: 0.05% or less, Si: 0.5% or less, Mn: 0.15-1.0%, P: 0.030% or less, S: 0.005% or less, Cr: 14.5-17.5%, Ni: 3.0-6.0%, Mo: 2.7-5.0%, Cu: 0.3-4.0%, W: 0.1- 2.5%, V: 0.02-0.20%, Al: 0.10% or less, N: 0.15% or less, B: 0.0005-0.0100%, and C, Si, Mn, Cr, Ni, Mo, Cu, N, W satisfy a specific relationship, and further have the following structure: in terms of volume ratio, it contains more than 45% of martensite phase as the main phase, contains 10-45% of ferrite phase as the second phase, and contains less than 30% of retained austenite phase. Thus, it is possible to obtain a yield strength YS: 862MPa or more, and a strength containing CO 2 , Cl - , H 2 High-strength stainless steel seamless pipe for oil wells that exhibits sufficient corrosion resistance even in severe corrosion environments at high temperatures.

[0008] In addition, Patent Document 4 proposes a high-strength stainless steel seamless steel pipe for oil wells, having the following composition: in terms of mass %, it contains C: less than 0.06%, Si: less than 1.0%, P: less than 0.05%, S: less than 0.005%, Cr: greater than 15.7% and less than 18.0%, Mo: 1.8% to 3.5%, Cu: 1.5% to 3.5%, Ni: 2.5% to 6.0%, Al: less than 0.10%, N: less than 0.10%, O: less than 0.010%, W: 0.5% to 2.0%, Co: 0.01% to 1.5%, C, Si, Mn, Cr, Ni, Mo, Cu, and N satisfy specific relationships, and further has the following structure: in terms of volume percentage, it contains 25% or more of a martensite phase, 65% or less of a ferrite phase, and 40% or less of a retained austenite phase. Thus, a yield strength YS of 758 MPa or more can be obtained, and a 2 , Cl - , H 2 High-strength stainless steel seamless pipe for oil wells that exhibits sufficient corrosion resistance even in severe corrosion environments at high temperatures.

[0009] In addition, in Patent Document 5, a high-strength stainless steel seamless steel pipe for oil wells is proposed, having the following composition: in terms of mass %, it contains C: less than 0.06%, Si: less than 1.0%, Mn: 0.01% to 1.0%, P: less than 0.05%, S: less than 0.005%, Cr: 15.2% to 18.5%, Mo: 1.5% to 4.3%, Cu: 1.1% to 3.5%, Ni: 3.0% to 6.5%, Al: less than 0.10%, N: less than 0.10%, O: less than 0.010%, Sn: 0.001% to 1.000%, and C, Si, Mn, Cr, Ni, Mo, Cu, and N satisfy specific relationships, and further has the following structure: in terms of volume ratio, it contains 30% or more of a martensite phase, 65% or less of a ferrite phase, and 40% or less of a retained austenite phase. Thus, a yield strength YS of 758 MPa or more can be obtained, and a 2 , Cl - High-strength stainless steel seamless pipe for oil wells that also exhibits sufficient corrosion resistance in harsh corrosive environments of high temperatures.

[0010] Patent document 6 proposes a high-strength stainless steel seamless steel pipe for oil wells, having the following composition: in mass %, it contains C: less than 0.06%, Si: less than 1.0%, Mn: 0.01% to 1.0%, P: less than 0.05%, S: less than 0.005%, Cr: 15.2% to 18.5%, Mo: 1.5% to 4.3%, Cu: 1.1% to 3.5%, Ni: 3.0% to 6.5%, Al: less than 0.10%, N: less than 0.10%, O: less than 0.010%, Sb: 0.001% to 1.000%, C, Si, Mn, Cr, Ni, Mo, Cu, and N satisfy specific relationships, and further has the following structure: in volume percentage, it contains 30% or more of a martensite phase, 65% or less of a ferrite phase, and 40% or less of a retained austenite phase. Thus, a yield strength YS of 758 MPa or more can be obtained, and a 2 , Cl - , H 2 High-strength stainless steel seamless pipe for oil wells that exhibits sufficient corrosion resistance even in severe corrosion environments at high temperatures.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: International Publication No. 2013 / 146046

[0014] Patent Document 2: International Publication No. 2017 / 168874

[0015] Patent Document 3: International Publication No. 2018 / 155041

[0016] Patent Document 4: International Publication No. 2021 / 065263

[0017] Patent Document 5: International Publication No. 2021 / 187330

[0018] Patent Document 6: International Publication No. 2021 / 187331 Summary of the invention

[0019] According to the prior art techniques proposed in Patent Documents 1 to 6, the corrosion resistance of stainless steel can be improved. However, the performance thereof is still insufficient.

[0020] That is, as described above, oil well steel pipes are required to have not only excellent yield strength and low-temperature toughness but also high corrosion resistance that allows them to withstand use in severe corrosive environments.

[0021] For example, oil well steel pipes are required to have corrosion resistance in a carbon dioxide environment (carbon dioxide corrosion resistance, CO 2Excellent corrosion resistance), especially excellent carbon dioxide corrosion resistance in high temperature environments.

[0022] In addition, oil well steel pipes are required to have the property of not causing sulfide stress cracking (Sulfidestress cracking: SSC) in a hydrogen sulfide environment (SSC resistance). In particular, in the case of submarine oil fields, the cold seawater is trapped near the seabed due to its high specific gravity, so the oil well pipes are exposed to temperatures lower than the atmospheric temperature in the area. Therefore, oil well steel pipes are required to have excellent SSC resistance in low temperature environments.

[0023] Furthermore, when oil is extracted, there are cases where the properties (mainly permeability) of the layer (storage layer) storing oil are poor and sufficient production cannot be obtained, and there are cases where the expected production cannot be obtained due to blockage in the storage layer. Therefore, as one of the methods for improving productivity, acid treatment (acidizing) of injecting acid such as hydrochloric acid into the storage layer is sometimes performed. Therefore, oil well steel pipes are also required to have excellent corrosion resistance in acid environments.

[0024] However, in the prior art, the actual situation is that it is not possible to obtain a steel pipe having sufficient levels of yield strength, low-temperature toughness, carbon dioxide corrosion resistance at high temperatures, SSC resistance at low temperatures, and corrosion resistance in acid environments.

[0025] In particular, the technology described in Patent Document 6 achieves high strength, corrosion resistance at high temperatures, and corrosion resistance in acidic environments, but is not necessarily sufficient for sulfide stress cracking resistance. The main factors are considered to be as follows. That is, when the phase fraction during steel pipe manufacturing is not appropriate, hot workability is insufficient, and cracks and cracks occur on the inner and outer surfaces of the steel pipe. When such a steel pipe is used in an oil well, corrosive ions are retained inside the defects and further concentrated as corrosion progresses, resulting in failure to exhibit sufficient SSC resistance.

[0026] The object of the present invention is to solve the problems of the prior art and to provide a stainless seamless steel pipe having both high strength of a yield strength of 758 MPa (110 ksi) or more and excellent low-temperature toughness and corrosion resistance.

[0027] In the present invention, “excellent corrosion resistance” means that “carbon dioxide corrosion resistance at high temperature”, “SSC resistance at low temperature”, and “corrosion resistance in an acid environment” are all excellent.

[0028] Here, "excellent carbon dioxide corrosion resistance at high temperature" means that the test piece is immersed in a test solution: a 20 mass % NaCl aqueous solution (solution temperature: 200°C, 30 atmospheres of CO2) maintained in an autoclave. 2When the immersion time was set to 336 hours in a gas atmosphere, the corrosion rate was less than 0.127 mm / y.

[0029] In addition, "excellent SSC resistance at low temperature" means that the following 2 Gas, 0.005 atmospheres of H 2 A C-shaped test piece according to NACE TM0177 Method C was immersed in an aqueous solution prepared by adding acetic acid + sodium acetate and adjusting the pH to 3.0 in a S atmosphere. The immersion time was set to 720 hours. The load stress was 100% of the yield stress. No cracks were generated in the test piece after the test.

[0030] Excellent "corrosion resistance in an acid environment" means that when the test piece is immersed in a 15 mass % hydrochloric acid solution heated to 80° C. for 40 minutes, the corrosion rate is 600 mm / y or less.

[0031] Excellent low temperature toughness refers to the Charpy absorbed energy vE at -10°C -10 The above Charpy absorbed energy vE -10 The measurement is carried out by the following steps. First, three V-notch test pieces (10 mm thick) are cut from a stainless steel seamless pipe according to the provisions of ASTM E23. The long side direction of the V-notch test piece is perpendicular to the pipe axis, and the notch is located on the surface perpendicular to the pipe axis. Then, these test pieces are used to perform a Charpy impact test at a test temperature of -10°C, and the lowest value of the absorbed energy of the three test pieces is taken as the Charpy absorbed energy vE at -10°C. -10 .

[0032] In order to achieve the above object, the present inventors have conducted in-depth research on various important factors affecting the corrosion resistance of stainless steel, especially SSC resistance and corrosion resistance in acid environments. As a result, it was found that excellent corrosion resistance can be obtained by containing Cr, Mo, Sn, Co, and Ca in a predetermined amount or more and limiting the amount of Ni that affects the phase fraction of steel to a predetermined range.

[0033] The present invention has been completed by further research based on this knowledge. That is, the gist of the present invention is as follows.

[0034] 1. A stainless steel seamless steel pipe having the following composition:

[0035] Contains, in mass%, C: 0.06% or less, Si: 1.0% or less, Mn: 0.01% to 1.0%, P: 0.05% or less, S: 0.005% or less, Cr: 15.2% to 18.0%, Mo: 1.5% to 4.3%, Cu: 1.2% to 3.5%, Ni: 3.5% to 5.2%, V: 0.5% or less, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, Sn: 0.001% to 1.000%, Co: 0.01% to 1.00%, and Ca: 0.001% to 0.030%, with the remainder being Fe and unavoidable impurities;

[0036] In terms of volume ratio, the martensite phase is 30% or more, the ferrite phase is 50% or less, and the retained austenite phase is 40% or less;

[0037] Yield strength is above 758MPa, Charpy absorbed energy vE at -10℃ -10 More than 40J.

[0038] 2. The stainless steel seamless pipe according to item 1 above, wherein:

[0039] The above-mentioned component composition further contains, in mass %, at least one selected from the group consisting of Nb: 0.07% or less, Ti: 0.2% or less, W: 0.5% or less, B: 0.01% or less, Ta: 0.3% or less, Zr: 0.3% or less, REM: 0.3% or less, Mg: 0.01% or less, and Sb: 1.0% or less.

[0040] 3. The stainless seamless steel pipe according to 1 or 2 above, wherein:

[0041] In terms of volume ratio, the martensite phase is 50% or more, the ferrite phase is 50% or less, and the retained austenite phase is 25% or less.

[0042] The yield strength is above 862MPa.

[0043] 4. A method for manufacturing a stainless steel seamless pipe, comprising the following steps:

[0044] A seamless steel pipe is produced from a steel billet having the composition described in 1 or 2 above.

[0045] The seamless steel pipe is heated to a quenching temperature of 850-1150°C.

[0046] The heated seamless steel pipe is cooled at a cooling rate of 0.01°C / s or more to a cooling stop temperature of 50°C or less.

[0047] The cooled seamless steel pipe is heated to a tempering temperature of 500 to 650° C.

[0048] The stainless seamless steel pipe has a martensite phase of 30% or more, a ferrite phase of 50% or less, and a retained austenite phase of 40% or less by volume.

[0049] Yield strength is 758MPa or more, Charpy absorbed energy vE at -10℃ -10 More than 40J.

[0050] 5. The method for manufacturing a stainless seamless steel pipe according to 4 above, wherein:

[0051] In terms of volume ratio, the martensite phase is 50% or more, the ferrite phase is 50% or less, and the retained austenite phase is 25% or less.

[0052] The yield strength is above 862MPa.

[0053] According to the present invention, it is possible to provide a stainless seamless steel pipe having both high strength of a yield strength of 758 MPa (110 ksi) or more and excellent low-temperature toughness and corrosion resistance. DETAILED DESCRIPTION

[0054] Hereinafter, the present invention will be described in detail.

[0055] [Ingredients]

[0056] The stainless seamless steel pipe of the present invention has the above-mentioned composition. First, the reasons for limiting the above-mentioned composition are explained. Hereinafter, "mass %" is abbreviated as "%" unless otherwise specified.

[0057] C: 0.06% or less

[0058] C is an element inevitably contained in the steelmaking process. If the C content exceeds 0.06%, the corrosion resistance decreases. Therefore, the C content is set to 0.06% or less. The C content is preferably 0.05% or less, more preferably 0.04% or less, and further preferably 0.03% or less. On the other hand, from the viewpoint of corrosion resistance, the lower the C content, the better, so the lower limit of the C content is not particularly limited. However, from the viewpoint of decarburization cost, the C content is preferably 0.002% or more, more preferably 0.003% or more, and further preferably 0.005% or more.

[0059] Si: 1.0% or less

[0060] Si is an element that functions as a deoxidizer. However, if Si is contained in an amount exceeding 1.0%, hot workability and corrosion resistance are reduced. Therefore, the Si content is set to 1.0% or less, preferably 0.7% or less, more preferably 0.5% or less, and further preferably 0.4% or less. On the other hand, the lower limit of the Si content is not particularly limited. From the viewpoint of improving the deoxidation effect, the Si content is preferably 0.03% or more, more preferably 0.05% or more, and further preferably 0.1% or more.

[0061] Mn: 0.01~1.0%

[0062] Mn is an element that acts as a deoxidizing material and a desulfurizing material to improve hot workability. In order to improve the strength while obtaining the effect of a deoxidizing and desulfurizing material, the Mn content is set to 0.01% or more, preferably 0.03% or more, more preferably 0.05% or more, and further preferably 0.1% or more. On the other hand, even if Mn is contained in excess of 1.0%, the effect is saturated. Therefore, the Mn content is set to 1.0% or less, preferably 0.8% or less, more preferably 0.6% or less, and further preferably 0.4% or less.

[0063] P: 0.05% or less

[0064] P is an element that reduces carbon dioxide corrosion resistance and SSC resistance. In order to obtain the desired corrosion resistance, the P content is set to 0.05% or less, preferably 0.04% or less, and more preferably 0.03% or less. On the other hand, the P content is preferably reduced as low as possible, so the lower limit of the P content is not particularly limited and can be 0%. However, excessive reduction leads to increased costs, so from the perspective of cost, the P content is preferably 0.005% or more, and more preferably 0.010% or more.

[0065] S: 0.005% or less

[0066] S is an element that significantly reduces hot workability and hinders stable operation of the hot pipe making process. In addition, S exists in steel as sulfide inclusions, which reduces corrosion resistance. Therefore, the S content is set to 0.005% or less, preferably 0.004% or less, more preferably 0.003% or less, and further preferably 0.002% or less. On the other hand, the S content is preferably reduced as much as possible, so the lower limit of the S content is not particularly limited and can be 0%. However, excessive reduction leads to increased costs, so from the perspective of cost, the S content is preferably 0.0003% or more, and more preferably 0.0005% or more.

[0067] Cr: 15.2~18.0%

[0068] Cr is an element that forms a protective film on the surface of the steel pipe and contributes to improving corrosion resistance. When the Cr content is less than 15.2%, the desired carbon dioxide corrosion resistance and sulfide stress cracking resistance cannot be ensured. Therefore, the Cr content is set to 15.2% or more, preferably 15.5% or more, more preferably 16.0% or more, and further preferably 16.30% or more. On the other hand, if the Cr content exceeds 18.0%, the ferrite fraction is too high and the desired strength cannot be ensured. Therefore, the Cr content is set to 18.0% or less, preferably 17.5% or less, more preferably 17.2% or less, and further preferably 17.0% or less.

[0069] Mo: 1.5~4.3%

[0070] Mo stabilizes the protective film on the surface of the steel pipe and increases the resistance to Cl - , and the resistance to pitting corrosion caused by low pH, thereby improving corrosion resistance. In order to obtain the desired corrosion resistance, the Mo content is set to 1.5% or more, preferably 1.8% or more, more preferably 2.0% or more, and further preferably 2.3% or more. On the other hand, when the Mo content exceeds 4.3%, the ferrite fraction is too high and the desired strength cannot be ensured. Therefore, the Mo content is set to 4.3% or less, preferably 4.0% or less, more preferably 3.5% or less, and further preferably 3.0% or less.

[0071] Cu: 1.2~3.5%

[0072] Cu has the effect of stabilizing the protective film on the surface of the steel pipe and improving the carbon dioxide corrosion resistance and sulfide stress cracking resistance. In order to obtain the desired strength and corrosion resistance, especially carbon dioxide corrosion resistance, the Cu content is set to 1.2% or more, preferably 1.8% or more, more preferably 2.0% or more, and further preferably 2.3% or more. On the other hand, if the Cu content is too high, the hot workability of the steel is reduced, and external surface defects are generated during pipe making, and the desired sulfide stress cracking resistance cannot be obtained. Therefore, the Cu content is set to 3.5% or less, preferably 3.2% or less, more preferably 3.0% or less, and further preferably 2.7% or less.

[0073] Ni: 3.5-5.2%

[0074] Ni improves the low temperature toughness of steel. In addition, Ni contributes to the increase of austenite fraction, thus affecting the hot workability during hot rolling. In order to obtain the desired toughness, the Ni content is set to 3.5% or more, preferably 3.8% or more, more preferably 4.0% or more, and further preferably 4.3% or more. On the other hand, when the Ni content exceeds 5.2%, the austenite fraction is too high and the hot workability of the steel is reduced. Furthermore, as a result, defects are easily generated during hot rolling, and the desired sulfide stress cracking resistance is sometimes not obtained. Therefore, the Ni content is set to 5.2% or less, preferably 5.0% or less.

[0075] V: 0.5% or less

[0076] V is an element that increases strength without compromising toughness by forming carbonitrides. In addition, V also has the effect of improving corrosion resistance. This is because V preferentially forms carbonitrides, thereby preventing corrosion-resistant elements such as Cr from forming carbonitrides and reducing the effective amount effective for corrosion resistance. However, even if V is contained in excess of 0.5%, its effect is saturated. Therefore, the V content is set to less than 0.5%, preferably less than 0.2%, and more preferably less than 0.1%. On the other hand, the lower limit of the V content is not particularly limited, but is preferably greater than 0.01%, and more preferably greater than 0.03%.

[0077] Al: 0.10% or less

[0078] Al is an element that functions as a deoxidizer. However, if Al is contained in an amount exceeding 0.10%, the corrosion resistance decreases. Therefore, the Al content is set to 0.10% or less, preferably 0.07% or less, and more preferably 0.05% or less. On the other hand, the lower limit of the Al content is not particularly limited, but from the viewpoint of high deoxidation effect, the Al content is preferably 0.005% or more, more preferably 0.01% or more, and further preferably 0.015% or more.

[0079] N: 0.10% or less

[0080] N is an element that is inevitably contained in the steelmaking process, but it is also an element that improves the strength of steel. However, if the N content exceeds 0.10%, the amount of nitride formed is excessive and the corrosion resistance is reduced. Therefore, the N content is set to 0.10% or less, preferably 0.07% or less, more preferably 0.05% or less, and further preferably 0.03% or less. On the other hand, the lower limit of the N content is not particularly limited, but an extreme reduction in the N content will lead to an increase in steelmaking costs. Therefore, the N content is preferably 0.002% or more, more preferably 0.003% or more, and further preferably 0.005% or more.

[0081] O: 0.010% or less

[0082] Since O (oxygen) exists in steel as an oxide, it has an adverse effect on various properties. Therefore, in the present invention, it is preferred to reduce the O content as much as possible. In particular, if the O content exceeds 0.010%, hot workability and corrosion resistance are reduced. Therefore, the O content is set to 0.010% or less. However, since excessive reduction leads to increased costs, from the perspective of cost, the O content is preferably 0.00005% or more, and more preferably 0.001% or more.

[0083] Sn: 0.001~1.000%

[0084] Sn is an element required to improve corrosion resistance in an acid environment. In order to obtain the desired corrosion resistance, the Sn content is set to 0.001% or more, preferably 0.003% or more, more preferably 0.005% or more, and further preferably 0.010% or more. On the other hand, even if Sn is contained in excess of 1.000%, the effect is saturated. Therefore, the Sn content is set to 1.000% or less, preferably 0.500% or less, more preferably 0.100% or less, and further preferably 0.050% or less.

[0085] Co: 0.01~1.00%

[0086] Co is an element that improves corrosion resistance. In order to obtain the desired corrosion resistance, the Co content is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, even if Co is contained in excess of 1.00%, the effect is saturated. Therefore, the Co content is set to 1.00% or less, preferably 0.50% or less, more preferably 0.30% or less, and further preferably 0.10% or less.

[0087] Ca: 0.001~0.030%

[0088] Ca is an element that improves hot workability by controlling the form of sulfides, and contributes to improving the SSC resistance of steel pipes by suppressing the generation of defects during pipe making. In order to obtain the above-mentioned effect, the Ca content is set to 0.001% or more, preferably 0.003% or more, more preferably 0.005% or more, more preferably more than 0.010%, further preferably 0.012% or more, and most preferably 0.014% or more. On the other hand, even if Ca is contained in excess of 0.030%, the effect is saturated, and an effect commensurate with the content cannot be expected. Therefore, the Ca content is set to 0.030% or less, preferably 0.025% or less, and more preferably 0.020% or less.

[0089] The stainless seamless steel pipe in one embodiment of the present invention has a composition containing the above components and the balance consisting of Fe and inevitable impurities.

[0090] In other embodiments of the present invention, the above-mentioned component composition may further arbitrarily contain at least one selected from Nb, Ti, W, B, Ta, Zr, REM, Mg and Sb. Nb, Ti, W, B, Ta, Zr, REM, Mg and Sb may be arbitrarily and selectively contained, and the lower limit of the content thereof may also be 0%.

[0091] Nb: 0.07% or less

[0092] Nb is an element that forms carbonitrides and further improves strength and corrosion resistance, and can be contained as needed. However, Nb carbonitrides tend to reduce low-temperature toughness, so when Nb is added, the Nb content is set to 0.07% or less, preferably 0.03% or less, and more preferably 0.01% or less. On the other hand, the lower limit of the Nb content can be 0%, but from the viewpoint of improving the effect of Nb addition, the Nb content is set to 0.001% or more.

[0093] Ti: 0.2% or less

[0094] Ti is an element that further improves strength and corrosion resistance and can be contained as needed. However, if more than 0.2% of Ti is contained, low-temperature toughness decreases. Therefore, when Ti is added, the Ti content is set to 0.2% or less, preferably 0.05% or less, and more preferably 0.01% or less. On the other hand, the lower limit of the Ti content can be 0%, but from the viewpoint of improving the effect of adding Ti, the Ti content is preferably 0.001% or more.

[0095] W: 0.5% or less

[0096] W is an element that helps to further improve the strength of steel and stabilize the protective film on the surface of the steel pipe to further improve the corrosion resistance. However, if W is contained in an amount exceeding 0.5%, the low temperature toughness decreases. Therefore, when W is added, the W content is set to 0.5% or less, preferably 0.3% or less, and more preferably 0.2% or less. On the other hand, the lower limit of the W content is not particularly limited, and may be 0%, preferably 0.05% or more, and more preferably 0.1% or more.

[0097] B: 0.01% or less

[0098] B is an element that contributes to the improvement of hot workability and has the effect of suppressing the generation of cracks and cracks during the pipe making process. However, if B is contained in an amount exceeding 0.01%, the low temperature toughness decreases. Therefore, when B is added, the B content is set to 0.01% or less, preferably 0.007% or less, and more preferably 0.005% or less. On the other hand, the lower limit of the B content is not particularly limited, and may be 0%, preferably 0.0005% or more, and more preferably 0.001% or more.

[0099] Ta: 0.3% or less

[0100] Ta is an element that further improves strength and has the effect of further improving corrosion resistance, and can be contained as needed. However, even if it is contained in excess of 0.3%, the effect is saturated. Therefore, when Ta is added, the Ta content is set to 0.3% or less. On the other hand, the lower limit of the Ta content is not particularly limited, and can be 0%, preferably 0.001% or more.

[0101] Zr: 0.3% or less

[0102] Zr is an element that further improves strength and can be contained as needed. In addition, Zr also has the effect of further improving SSC resistance. However, even if Zr is contained in excess of 0.3%, the effect is saturated. Therefore, when Zr is added, the Zr content is set to 0.3% or less. On the other hand, the lower limit of the Zr content is not particularly limited and can be 0%, preferably 0.0005% or more.

[0103] REM: 0.3% or less

[0104] REM (rare earth metal) is an element that helps to further improve the resistance to sulfide stress cracking by controlling the morphology of sulfides, and can be contained as needed. However, even if it is contained in an amount exceeding 0.3%, the effect is saturated, and an effect consistent with the content cannot be expected. Therefore, when REM is added, the REM content is set to 0.3% or less. On the other hand, the lower limit of the REM content is not particularly limited, and may be 0%, but is preferably greater than 0.0005%. It should be noted that the REM referred to in the present invention refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanide elements from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The composition of the stainless steel seamless pipe of the present invention may arbitrarily contain at least one of the above-mentioned REM. The REM content in the present invention refers to the total content of the above-mentioned elements.

[0105] Mg: 0.01% or less

[0106] Mg is an element that further improves corrosion resistance and can be contained as needed. However, even if it is contained in an amount exceeding 0.01%, the effect is saturated and an effect consistent with the content cannot be expected. Therefore, when Mg is added, the Mg content is set to 0.01% or less. On the other hand, the lower limit of the Mg content is not particularly limited and can be 0%, preferably 0.0005% or more.

[0107] Sb: 1.0% or less

[0108] Sb is an element that further improves corrosion resistance and can be contained as needed. However, even if it is contained in an amount exceeding 1.0%, the effect is saturated and an effect consistent with the content cannot be expected. Therefore, when Sb is contained, the Sb content is set to 1.0% or less. On the other hand, the lower limit of the Sb content is not particularly limited and can be 0%, preferably 0.001% or more.

[0109] [organize]

[0110] Next, the reasons for limiting the structure of the stainless seamless steel pipe of the present invention will be described.

[0111] In the stainless seamless steel pipe according to one embodiment of the present invention, the martensite phase accounts for 30% or more, the ferrite phase accounts for 50% or less, and the retained austenite phase accounts for 40% or less by volume.

[0112] Martensite phase: more than 30%

[0113] If the volume fraction of the martensite phase is less than 30%, the desired strength cannot be ensured. Therefore, the volume fraction of the martensite phase is 30% or more, preferably 40% or more, more preferably 45% or more, and further preferably 50% or more. On the other hand, the upper limit of the volume fraction of the martensite phase is not particularly limited, but is preferably 90% or less, and more preferably 85% or less.

[0114] Ferrite phase: less than 50%

[0115] By containing a ferrite phase, the progress of sulfide stress corrosion cracking and sulfide stress cracking can be suppressed, and excellent corrosion resistance can be obtained. However, if the volume fraction of the ferrite phase exceeds 50%, the desired strength cannot be ensured. Therefore, the volume fraction of the ferrite phase is set to 50% or less, preferably 40% or less, and more preferably 35% or less. On the other hand, the lower limit of the volume fraction of the ferrite phase is not particularly limited, but is preferably 10% or more, more preferably 15% or more, and further preferably 20% or more.

[0116] Retained austenite phase: less than 40%

[0117] Due to the presence of the retained austenite phase, ductility and low temperature toughness are improved. However, if a large amount of austenite phase exceeding 40% by volume is precipitated, the desired strength cannot be ensured. Therefore, the retained austenite phase is 40% or less by volume, preferably 30% or less, and more preferably 25% or less. On the other hand, the lower limit of the volume fraction of the retained austenite phase is not particularly limited, but is preferably 3% or more, and more preferably 5% or more.

[0118] Here, the volume ratio of each phase is determined by the following method. First, a test piece for tissue observation cut from a stainless steel seamless pipe is corroded with a Villier reagent (a reagent prepared by mixing picric acid, hydrochloric acid and ethanol in proportions of 2 g, 10 ml and 100 ml, respectively). Next, a scanning electron microscope (SEM) is used to photograph the structure of the test piece for tissue observation at a magnification of 1000 times to obtain a SEM image. The obtained SEM image is analyzed using image analysis software (ImageJ 1.52p, National Institute of Health) to calculate the tissue fraction (area ratio (%)) of the ferrite phase. In the above analysis, the SEM image is binarized, and the area with low brightness is regarded as the ferrite phase. The area ratio obtained by the above steps is defined as the volume ratio (%) of the ferrite phase.

[0119] Next, the X-ray diffraction test piece cut from the stainless steel seamless pipe was ground and polished in such a way that the cross section (C cross section) perpendicular to the pipe axis direction was used as the measurement surface, and the structure fraction of the retained austenite (γ) phase was measured using the X-ray diffraction method. Specifically, the volume fraction of the retained austenite phase was calculated using the following formula based on the integrated intensity of the (220) plane of austenite and the (211) plane of ferrite.

[0120] Vγ(%)=100 / (1+(IαRγ / IγRα))

[0121] in,

[0122] Vγ: volume fraction of retained austenite phase,

[0123] Iα: integrated intensity of the (211) plane of ferrite,

[0124] Iγ: integrated intensity of the (220) plane of austenite,

[0125] Rα: The crystallographic theoretical calculated value of α (34.15),

[0126] Rγ: The crystallographically calculated value of γ (22.33).

[0127] The remaining portion other than the ferrite phase and the retained γ phase determined by the above-mentioned measuring method is regarded as the fraction of the martensite phase. The method of observing the above-mentioned structures will be described in detail in the examples described later.

[0128] It should be noted that, as described above, the structure of the stainless seamless steel pipe of the present invention is substantially composed of a martensite phase, a ferrite phase, and a retained austenite phase. That is, the above structure may also contain other structures within the range that does not impair the effects of the present invention. Examples of the above other structures include intermetallic compounds and inclusions.

[0129] In other words, the stainless seamless steel pipe according to one embodiment of the present invention may also have the following structure: in terms of volume ratio,

[0130] Contains less than 50% of a ferrite phase and less than 40% of a retained austenite phase, with the remainder being substantially composed of a martensite phase, and,

[0131] The volume fraction of the martensite phase is 30% or more.

[0132] In addition, the stainless seamless steel pipe according to another embodiment of the present invention may also have the following structure: by volume ratio,

[0133] It is composed of more than 30% of martensite phase, less than 50% of ferrite phase and less than 40% of retained austenite phase.

[0134] However, in any case, it is allowed that the above structure contains an impurity phase that is inevitably present.

[0135] Yield strength: 758MPa or more

[0136] The stainless steel seamless pipe of the present invention has a yield strength of 758 MPa or more. The upper limit of the yield strength is not particularly limited, but is preferably 1034 MPa or less. The yield strength can be measured by a tensile test. More specifically, it can be measured by the method described in the examples.

[0137] v -10 : 40J or more

[0138] The Charpy absorbed energy vE of the stainless steel seamless pipe of the present invention at -10°C -10 is 40J or more. -10 The higher the better, so the upper limit is not particularly limited, for example, it can be 300 J or less, or 250 J or less. The Charpy absorbed energy can be measured by a Charpy impact test. More specifically, it can be measured by the method described in the examples.

[0139] The stainless seamless steel pipe of the present invention is not particularly limited and can be used in any application, but is particularly suitable for oil wells. That is, the stainless seamless steel pipe of one embodiment of the present invention is a stainless seamless steel pipe for oil wells (high-strength stainless seamless steel pipe for oil wells).

[0140] [Manufacturing method]

[0141] Next, a suitable method for producing the stainless seamless steel pipe of the present invention will be described.

[0142] The stainless seamless steel pipe of the present invention can be produced by manufacturing a seamless steel pipe from a steel billet and subjecting the seamless steel pipe to a quenching-tempering treatment under specific conditions.

[0143] The steel billet is not particularly limited, and any billet can be used. Typically, a steel billet can be used. A billet having the above-mentioned component composition can be used.

[0144] The manufacturing method of the above-mentioned steel billet is not particularly limited and can be manufactured by any method. For example, molten steel having the above-mentioned composition is smelted by a smelting method such as a converter, and then made into a steel billet such as a steel billet by a method such as a continuous casting method or an ingot casting-blowing method.

[0145] [Pipe making]

[0146] The steel billet is piped to form a seamless steel pipe. The pipe-making method is not particularly limited and can be performed by any method. The pipe-making is preferably performed by hot working. In the case of pipe-making by hot working, the steel billet can be heated and then formed into a seamless steel pipe by hot working. The heating temperature in the heating is not particularly limited, but is preferably 1100 to 1350°C from the viewpoint of achieving both hot workability during pipe-making and low-temperature toughness of the final product at a high level.

[0147] The method of processing a steel billet into a seamless steel pipe is not particularly limited, and any method may be used. For example, a seamless steel pipe may be obtained by any of the Mannesmann rolling mill method and the Mannesmann mandrel mill method.

[0148] When the pipe is made by hot working, a cooling treatment may be performed after the pipe is made. The cooling treatment is not particularly limited and may be performed under any conditions. For example, it is preferred to cool to room temperature after the hot working. The cooling rate in the cooling is not particularly limited and may be cooled at any rate. For example, cooling may be performed at a cooling rate of air cooling.

[0149] [Quenching-tempering treatment]

[0150] Next, the obtained seamless steel pipe is subjected to a heat treatment consisting of a quenching treatment and a tempering treatment under specific conditions (quenching-tempering treatment). The conditions of the quenching-tempering treatment will be described below.

[0151] Quenching treatment

[0152] First, the seamless steel pipe is heated to a quenching temperature of 850 to 1150° C., and the heated seamless steel pipe is cooled to a cooling stop temperature of 50° C. or less at a cooling rate of 0.01° C. / s or more.

[0153] Quenching temperature: 850~1150℃

[0154] When the heating temperature (quenching temperature) in the quenching treatment is less than 850°C, the reverse phase transformation from martensite to austenite does not occur, and the phase transformation from austenite to martensite does not occur during cooling, and the desired strength cannot be ensured. Therefore, the quenching temperature is set to 850°C or more, preferably 900°C or more. On the other hand, if the quenching temperature is higher than 1150°C, the grains coarsen, and as a result, the low-temperature toughness deteriorates. Therefore, the quenching temperature is set to 1150°C or less, preferably 1100°C or less.

[0155] In the above quenching treatment, after the seamless steel pipe is heated to the above quenching temperature, a soaking treatment can be performed while maintaining the quenching temperature. By performing soaking treatment, the temperature of the seamless steel pipe in the wall thickness direction is uniform, which can reduce the deviation of the material. The time (soaking time) maintained at the quenching temperature is not particularly limited, and is preferably 5 to 30 minutes.

[0156] Cooling speed: 0.01℃ / s or more

[0157] If the cooling rate in the quenching treatment is less than 0.01°C / s, the desired structure cannot be obtained. Therefore, the cooling rate is set to be 0.01°C / s or more, preferably 1.0°C / s or more, more preferably 5.0°C / s or more, and further preferably 10.0°C / s or more. On the other hand, the upper limit of the above cooling rate is not particularly limited, but is preferably 100°C / s or less, more preferably 50°C / s or less, and further preferably 30°C / s or less.

[0158] The cooling is not particularly limited and may be performed by any method. For example, the cooling is preferably performed by at least one of air cooling and water cooling, and more preferably by water cooling.

[0159] Cooling stop temperature: below 50℃

[0160] If the cooling stop temperature is higher than 50°C, the desired structure cannot be obtained. That is, if the cooling stop temperature is high, the phase transformation from austenite to martensite will not occur sufficiently, and the retained austenite fraction is excessive. Therefore, the cooling stop temperature in the quenching treatment is set to 50°C or less. On the other hand, the lower limit of the cooling stop temperature is not particularly limited, for example, it can be 0°C or more. It should be noted that the cooling stop temperature here is the surface temperature of the seamless steel pipe.

[0161] Tempering

[0162] Next, the seamless steel pipe after the quenching treatment is subjected to a tempering treatment in which the seamless steel pipe is heated to a tempering temperature of 500 to 650°C.

[0163] Tempering temperature: 500~650℃

[0164] If the tempering temperature is less than 500°C, sufficient tempering effect cannot be obtained, and as a result, low-temperature toughness deteriorates. Therefore, the tempering temperature is 500°C or higher, preferably 520°C or higher. On the other hand, if the tempering temperature is higher than 650°C, many intermetallic compounds precipitate, and excellent low-temperature toughness cannot be obtained. Therefore, the tempering temperature is 650°C, preferably 630°C or lower.

[0165] In the tempering treatment, the seamless steel pipe may be heated to the tempering temperature and then maintained at the tempering temperature. The time for maintaining the tempering temperature (maintaining time) is not particularly limited, but is preferably 5 minutes or more from the viewpoint of making the temperature in the wall thickness direction uniform and preventing the material from changing. On the other hand, the upper limit of the holding time is also not particularly limited, but is preferably 90 minutes or less.

[0166] After the above-mentioned tempering treatment, the steel may be allowed to cool.

[0167] By performing the quenching and tempering treatment described above, it is possible to obtain a stainless seamless steel pipe having desired strength and excellent low-temperature toughness and corrosion resistance.

[0168] Example

[0169] Hereinafter, the present invention will be further described based on examples. It should be noted that the present invention is not limited to the following examples.

[0170] First, a seamless steel pipe was produced from a steel billet having the chemical compositions shown in Tables 1 to 3 in the following manner.

[0171] The steel billet was cast using molten steel having the composition shown in Tables 1 to 3. Then, the steel billet was heated and hot-worked using a seamless rolling mill to form a seamless steel pipe with an outer diameter of 177.8 mm and a wall thickness of 16.0 mm, and then air-cooled. At this time, the heating temperature of the steel billet before hot working was set to 1250°C.

[0172] Next, the obtained seamless steel pipe was subjected to quenching-tempering treatment under the following conditions to obtain a stainless seamless steel pipe.

[0173] Quenching

[0174] The obtained seamless steel pipe was subjected to quenching treatment under the conditions shown in Tables 4 to 6. That is, the seamless steel pipe was heated to the quenching temperature shown in Tables 4 to 6, and maintained at the quenching temperature during the soaking time shown in Tables 3 and 4. Then, it was cooled to a cooling stop temperature of 5° C. at the cooling rate shown in Tables 4 to 6. The above cooling was performed by water cooling.

[0175] Tempering

[0176] Then, the cooled seamless steel pipe was heated to the tempering temperature shown in Tables 4 to 6, and maintained at the tempering temperature for the holding time shown in Tables 4 to 6. Then, the seamless steel pipe was air-cooled (let to cool). The cooling rate in the air cooling was 0.04°C / s.

[0177] Test pieces were cut from the obtained seamless stainless steel pipes and subjected to microstructure observation, tensile test, Charpy impact test and corrosion resistance test. The test methods are as follows.

[0178] (1) Organizational Observation

[0179] From the obtained seamless stainless steel pipe, a test piece for tissue observation is cut in such a way that the cross section including the tube axis direction and the wall thickness direction is the observation surface. The test piece for tissue observation is corroded with Villier's reagent (a reagent prepared by mixing picric acid, hydrochloric acid and ethanol in the proportions of 2g, 10ml and 100ml respectively), and the tissue is photographed by a scanning electron microscope (SEM) at a magnification of 1000 times to obtain a SEM image. The obtained SEM image is analyzed using image analysis software (ImageJ 1.52p, National Institute of Health) to calculate the tissue fraction (area ratio (%)) of the ferrite phase. In the above analysis, the SEM image is binarized, and the area with low brightness is regarded as the ferrite phase. The area ratio obtained by the above steps is taken as the volume ratio (%) of the ferrite phase.

[0180] In addition, a test piece for X-ray diffraction was cut from the obtained seamless stainless steel pipe, and the cross section (C cross section) perpendicular to the pipe axis direction was ground and polished as the measurement surface, and the structure fraction of the retained austenite (γ) phase was measured using the X-ray diffraction method. Specifically, the volume fraction of the retained austenite phase was calculated using the following formula based on the integrated intensity of the (220) plane of austenite and the (211) plane of ferrite.

[0181] Vγ(%)=100 / (1+(IαRγ / IγRα))

[0182] in,

[0183] Vγ: volume fraction of retained austenite phase,

[0184] Iα: integrated intensity of the (211) plane of ferrite,

[0185] Iγ: integrated intensity of the (220) plane of austenite,

[0186] Rα: The crystallographic theoretical calculated value of α (34.15),

[0187] Rγ: The crystallographically calculated value of γ (22.33).

[0188] The volume ratio of each phase obtained by the above steps is shown in Tables 4 to 6. In addition, the symbols M, F, and γ of the structures described in Tables 4 to 6 represent the following phases, respectively.

[0189] M: Martensite phase

[0190] F: Ferrite phase

[0191] γ: Retained austenite phase

[0192] (2) Tensile test

[0193] From the obtained seamless stainless steel pipe, an arc tensile test piece is cut in accordance with the provisions of API (American Petroleum Institute)-5CT with the pipe axis direction as the tensile direction, and a tensile test is performed to obtain the yield strength (YS). Here, the case where the yield strength YS is 758MPa or more is high strength and is qualified, and the case where it is less than 758MPa is unqualified.

[0194] (3) Charpy impact test

[0195] In order to evaluate the low-temperature toughness, a Charpy impact test was carried out by the following procedure.

[0196] First, from the obtained stainless steel seamless pipe, according to the provisions of ASTM E23, a V-notch test piece (10 mm thick) with the long side of the test piece perpendicular to the pipe axis and the notch located on the surface perpendicular to the pipe axis is cut. Using the above test piece, a Charpy impact test is carried out at a test temperature of -10°C. In the above test, three test pieces are cut from a stainless steel seamless pipe, and the absorbed energy of each test piece is measured. The lowest value of the absorbed energy of the three test pieces is taken as the Charpy absorbed energy vE at -10°C. -10 . -10 The case of 40 J or more was regarded as passing.

[0197] (4) Carbon dioxide corrosion resistance test

[0198] In order to evaluate the carbon dioxide corrosion resistance at high temperature, the following test was performed.

[0199] From the obtained seamless stainless steel pipe, a corrosion test piece with a thickness of 3 mm × a width of 30 mm × a length of 40 mm was made by mechanical processing. The corrosion test piece was used to carry out a corrosion test, and the corrosion rate as an indicator of carbon dioxide corrosion resistance was measured. The corrosion test was carried out as follows: the test piece was immersed in the test solution maintained in the above autoclave: a 20 mass% NaCl aqueous solution (solution temperature: 200°C, 30 atmospheres of CO2 Gas atmosphere), and the immersion period is set to 14 days (336 hours). The weight of the corrosion test piece after the above corrosion test is measured, and the weight of the test piece before the corrosion test measured in advance is subtracted to calculate the weight loss caused by the corrosion test. Next, the weight loss per unit time and unit area is obtained by dividing the above weight loss by the surface area of ​​the test piece used and the above immersion period. Furthermore, the above weight loss per unit time and unit area is divided by the density of steel to convert it into the corrosion thickness per unit time and unit area. The corrosion thickness per unit time and unit area (mm / y) thus obtained is used as the corrosion rate in carbon dioxide. Here, the case where the above corrosion rate is 0.127mm / y or less is qualified, and the case where it exceeds 0.127mm / y is unqualified.

[0200] (5) SSC resistance test

[0201] In order to evaluate the SSC resistance at low temperature, the following test was performed.

[0202] From the obtained seamless stainless steel pipe, a C-shaped test piece was prepared by machining in accordance with NACE TM0177 Method C, and an SSC resistance test was performed. It should be noted that the curved surfaces corresponding to the inner and outer surfaces of the steel pipe were not ground or polished.

[0203] The SSC resistance test was carried out as follows: in a 0.165 mass % NaCl aqueous solution (solution temperature: 7° C., 0.995 atmospheric pressure CO 2 Gas, 0.005 atmospheres of H 2 The test piece was immersed in an aqueous solution of acetic acid + sodium acetate added to the solution in an S atmosphere and adjusted to pH 3.0 according to NACE TM0177 Method C. The immersion time was set to 720 hours, and the load stress was 100% of the yield stress. Here, the case without cracks was regarded as qualified, and the case with cracks was regarded as unqualified. In Tables 4 to 6, qualified is represented by "1" and unqualified is represented by "2".

[0204] (6) Corrosion test in acid environment

[0205] In order to evaluate the corrosion resistance in an acid environment, the following test was performed.

[0206] First, a rectangular test piece is made from the obtained seamless stainless steel pipe by machining. The dimensions of the test piece are set to be 50 mm in length in the long side direction of the steel pipe, 3 mm in thickness in the wall thickness direction of the steel pipe, and 25 mm in width. After measuring the weight of the test piece, the test piece is immersed in a 15% by mass hydrochloric acid solution heated to 80°C for 40 minutes to perform a corrosion test. The weight of the test piece after the corrosion test is measured, and the weight of the test piece before the corrosion test is subtracted to obtain the weight reduction caused by the corrosion test. Next, the weight reduction per unit time and unit area is obtained by dividing the weight reduction by the surface area of ​​the test piece used and the immersion time in the corrosion test. Furthermore, the weight reduction per unit time and unit area is divided by the density of the steel to convert it into the corrosion thickness per unit time and unit area. The corrosion thickness per unit time and unit area (mm / y) obtained in this way is used as the corrosion rate in the acid environment. Here, the case where the etching rate is 600 mm / y or less is considered acceptable, and the case where the etching rate exceeds 600 mm / y is considered unacceptable.

[0207] (7) Hot workability

[0208] In addition, in order to evaluate the hot workability of the obtained seamless stainless steel pipe, the following evaluation was performed. The defect depth of the surface located on the outer side of the steel pipe of the test piece of the above-mentioned SSC resistance test was measured by ultrasonic flaw detection. Based on the maximum value of the measured defect depth, the hot workability was evaluated according to the following three levels.

[0209] 1: Maximum defect depth is less than 0.1mm

[0210] 2: Maximum defect depth exceeds 0.1mm and is less than 0.2mm

[0211] 3: Maximum defect depth exceeds 0.2mm

[0212] The obtained results are shown in Tables 4 to 6. As can be seen from the results shown in Tables 4 to 6, the stainless seamless steel pipes that meet the conditions of the present invention have both high strength of yield strength: 758 MPa (110 ksi) or more and excellent low-temperature toughness and corrosion resistance. In particular, regarding corrosion resistance, "carbon dioxide corrosion resistance at high temperature", "SSC resistance at low temperature" and "corrosion resistance in acid environment" are all excellent. Therefore, the stainless seamless steel pipe of the present invention can be particularly suitably used for various purposes, including oil well steel pipes.

[0213] Furthermore, in the inventive example in which the Ca content exceeds 0.010%, the maximum value of the defect depth is less than 0.1 mm. This result shows that the hot workability is significantly excellent, especially when the Ca content exceeds 0.010%. Therefore, if the Ca content exceeds 0.010%, it can be said that the SSC resistance at low temperature is more excellent.

[0214]

[0215]

[0216]

[0217]

[0218]

[0219]

Claims

1. A stainless steel seamless steel pipe having the following composition composition: Contains, in mass%, C: 0.06% or less, Si: 1.0% or less, Mn: 0.01% to 1.0%, P: 0.05% or less, S: 0.005% or less, Cr: 15.2% to 18.0%, Mo: 1.5% to 4.3%, Cu: 1.2% to 3.5%, Ni: 3.5% to 5.2%, V: 0.5% or less, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, Sn: 0.001% to 1.000%, Co: 0.01% to 1.00%, and Ca: 0.001% to 0.030%, with the remainder being Fe and unavoidable impurities; In terms of volume ratio, the martensite phase is 30% or more, the ferrite phase is 50% or less, and the retained austenite phase is 40% or less; Yield strength is above 758MPa, Charpy absorbed energy vE at -10℃ -10 More than 40J.

2. The stainless steel seamless pipe according to claim 1, wherein: The component composition further contains, in mass %, at least one selected from the group consisting of Nb: 0.07% or less, Ti: 0.2% or less, W: 0.5% or less, B: 0.01% or less, Ta: 0.3% or less, Zr: 0.3% or less, REM: 0.3% or less, Mg: 0.01% or less, and Sb: 1.0% or less.

3. The stainless seamless steel pipe according to claim 1 or 2, wherein: In terms of volume ratio, the martensite phase is 50% or more, the ferrite phase is 50% or less, and the retained austenite phase is 25% or less. The yield strength is above 862MPa.

4. A method for manufacturing a stainless steel seamless pipe, comprising the following steps: A seamless steel pipe is produced from a steel billet having the composition of claim 1 or 2, The seamless steel pipe is heated to a quenching temperature of 850 to 1150°C. The heated seamless steel pipe is cooled to a cooling stop temperature of 50° C. or less at a cooling rate of 0.01° C. / s or more, The cooled seamless steel pipe is heated to a tempering temperature of 500 to 650° C. The stainless seamless steel pipe has a martensite phase of 30% or more, a ferrite phase of 50% or less, and a retained austenite phase of 40% or less by volume. Yield strength is 758MPa or more, Charpy absorbed energy vE at -10℃ -10 More than 40J.

5. The method for manufacturing a stainless seamless steel pipe according to claim 4, wherein: In terms of volume ratio, the martensite phase is 50% or more, the ferrite phase is 50% or less, and the retained austenite phase is 25% or less. The yield strength is above 862MPa.

Citation Information

Patent Citations

  • Stainless steel for oil wells and stainless steel pipe for oil wells

    WO2013146046A1

  • High-strength seamless stainless-steel pipe for oil well

    WO2017168874A1

  • High strength seamless stainless steel pipe for oil well and production method therefor

    WO2018155041A1

  • Stainless seamless steel pipe and method for producing same

    WO2021065263A1

  • Stainless seamless steel pipe and method for producing stainless seamless steel pipe

    WO2021187330A1